Iron-Catalyzed Oxidative C–C and C–O Coupling of Halophenols to α-Substituted β-Keto Esters - Regev, Almog; Shalit, Hadas; Pappo, Doron (Synthesis, 2015)
The iron-catalyzed oxidative cross-coupling of halophenols to α-substituted β-keto esters takes place through one of two modes: oxidative C–C coupling or oxidative C–O coupling. A mechanistic investigation revealed that the chemoselectivity of these reactions is determined by the electronic and steric properties of the two coupling partners.
Keywords: iron; catalysis; cross-coupling; phenols; ketones; esters